2005
DOI: 10.1038/sj.bjc.6602500
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to the 105AD7 human anti-idiotypic vaccine after intensive chemotherapy, for osteosarcoma

Abstract: 105AD7 is a human monoclonal antibody that mimics the complement regulatory protein, CD55, overexpressed by many solid tumours including osteosarcoma. This study was designed to assess the toxicity and efficacy of this vaccine in a young age group of patients within 1 -6 months of myleosuppressive chemotherapy. Out of 28, 20 (71%, 95% CI 51 -87%) patients showed a significant T-cell proliferation response in vitro to the 105AD7 protein but not to human IgG. Furthermore, 13 out of 22 (59%, 95% CI 36 -79%) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…We have shown that a human monoclonal IgG1 anti-idiotypic Ab, which expressed a T-cell mimotope of CD55 Ag within its CDR, can stimulate helper and cytotoxic T-cell responses in over 300 cancer patients with no associated toxicity [20][21][22]. Two of the osteosarcoma patients were cured of their disease and survived for at least 10 years post treatment.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that a human monoclonal IgG1 anti-idiotypic Ab, which expressed a T-cell mimotope of CD55 Ag within its CDR, can stimulate helper and cytotoxic T-cell responses in over 300 cancer patients with no associated toxicity [20][21][22]. Two of the osteosarcoma patients were cured of their disease and survived for at least 10 years post treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A complete set of cryopreserved (À85jC) PBMC for each patient was defrosted for simultaneous analysis. The PBMCs were stimulated with the optimal concentration of 105AD7 (10 Ag/mL), positive control purified protein derivative (10 Ag/mL), or negative control human IgG antibody (10 Ag/mL) in RPMI 1640 containing 5% autologous human plasma with 1 mL/well (10 6 cells/mL) in 24-well plates (Corning, Inc., Corning, NY) as described previously (7). Soluble CD55 has been shown to inhibit proliferative responses and therefore was not included in these assays.…”
Section: Methodsmentioning
confidence: 99%
“…Work has since focused on the use of 105AD7 in the neoadjuvant/ adjuvant setting where patients in a phase I trial undergoing potentially curative surgery receiving preoperative immunizations showed enhanced infiltration of CD4 and CD8 lymphocytes and natural killer cells in their resected tumors when compared with matched controls (6). In a recent sarcoma trial, the potency of this vaccine concept was underlined by two long lasting clinical responses (7).…”
mentioning
confidence: 99%
“…An alternative approach is to use vaccines consisting of peptide alone. A trial has been published reporting that 105AD7, a human monoclonal antibody that mimics the complement regulatory protein CD55 that is frequently overexpressed in OS, was well-tolerated in younger patients exhibiting OS, and was capable of inducing a T-cell proliferation response and antigen-specific IFN-γ secretion (77). In a similar study utilizing SYT-SSX-derived peptide vaccines in patients exhibiting advanced synovial sarcoma, the administration of vaccine with incomplete Freund's adjuvant led to improved stable disease in patients, compared with those treated with vaccine alone (78).…”
Section: Vaccinesmentioning
confidence: 99%